Future power energy: wind power - Sharma, Richa (New Delhi The Energy and Resource Institute, 2008)
Can you imagine having no petrol for your car? Can you imagine no electricity to power your lights, fridge, and television? The fuels we use today are going to be over sooner or later. They are also causing pollution. We need clean and renewable sources of energy.This book takes a close look at wind power as a future source of power
Keywords: Wind power